Anterior Urethral Polyp – A Rare Cause of Urethrorrhagia - Chatterjee, Souvik; Sharma, Pramod Kumar; Samanta, Kanishka; Mandal, Soumendra Nath; Karmakar, Dilip (Bangladesh Journal of Medical Science, 2019)
Urethrorrhagia is a benign self limited condition. Most of the cases of urethrorrhagia are idiopathic. Anterior urethral polyp (AUP) is a rare cause of it. AUP most commonly affect infants. Endoscopic modality is the best way to detect as well as manage the polyps. Fibroepithelial polyps are benign in nature with no propensity of recurrence with complete excision. Bangladesh Journal of Medical Science Vol.18(3) 2019 p.663-664